Development of a pollution prevention methodology for the metalcasting industry - Naylor, Tara J. (Cranfield University, 2001)
The metalcasting industry consists of small businesses that cast a wide variety of metals and use many different casting processes. The metalcasting industry is a large recycler of metal, however, metalcasting is energy intensive and produces significant air, land and water emissions. The industry is vulnerable to the cost of conforming to increasingly stringent environmental regulations. Improving environmental performance while keeping regulatory costs to a minimum is one of the key challenges of the industry. An adaptable methodology is required that is usable by small manufacturing units in order to comply with environmental regulation in a cost-effective manner. The processes used in the metalcasting industry were investigated. The available energy, waste, materials consumption data and the industry environmental effects were reviewed and evaluated. The methodologies used to reduce pollution to a minimum in other industries were evaluated for: applicability to environmental issues, suitability to both high production and jobbing shops, applicability to different casting methods, ease of use by foundry and environmental personnel, data availability. The methods assessed included: preliminary assessment methods, process flowsheets, mass and energy balances, manufacturing process understanding, process integration, pinch methods, exergy analyses, life-cycle assessment and total cost assessment. The developed methodology is presented in the form of a flowchart that combines an ordered sequence, with appropriate feedback loops, of the selected methods. The developed methodology was successfully tested at a working non-ferrous metalcasting facility. Fluoride chemicals, added to sand moulds and cores to prevent casting defects, were creating large quantities of hazardous solid waste and air emissions from the sand system. The application of the methodology resulted in the identification of a modified process that added the fluoride chemical in a surface coating only, thus reducing emissions by 99%. This methodology can be used to reduce waste, material and resource use in the metalcasting industry.